Students Errors of Using Suffix ‘-S’, ‘-ES’ in Writing Simple Present Tense - Annisah, Annisah; Roza, Veni (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2022)
This research aimed to determine and to describe the students’ error of using suffix ‘-s’, ‘-es’ writing in simple present tense. This research was designed as form of qualitative research, particularly in writing simple present tense. The subject of this research is class VII that consists of 30 students. The data were collected using observation, tests, and interviews as the research instrument. The results showed that the student's comprehension in using suffix ‘-s’, ‘-es’ categorized as “good”, with a total score of 47%. The recommendation of this research is the students can improve their skill about how to use the suffix ‘-s’, and ‘-es’ of simple present tense.